Markov Chain-Based Analysis and Fault Tolerance Technique for Enhancing Chain-Based Routing in Wsns - Fernandez-Campusano, C (John Wiley and Sons Ltd, 2024)
Wireless sensor networks (WSNs) are faced with the challenge of energy conservation, which makes efficient routing protocols crucial for prolonging network lifetime. In addition, delay time from sensors to the base station is critical in applications such as military, medical, and security monitoring systems. Chain-based protocols like PEGASIS, CCBRP, and CCM have been developed to address routing in WSNs, with the aim of reducing energy consumption and delay. However, node failures are inevitable due to energy reduction and node mobility. Therefore, fault tolerance techniques must be integrated into routing protocols. A new fault tolerance method has been proposed to prevent early chain failures in WSNs by formulating network availability and reliability using Markov chain analysis. The results indicate that chain-based routing protocols with one spare node are more reliable than those with two spare nodes. © 2024 John Wiley & Sons Ltd.